Living the End of Antiquity Individual Histories from Byzantine to Islamic Egypt - Huebner, Sabine R.; Garosi, Eugenio; Marthot-Santaniello, Isabelle; Müller, Matthias; Stern, Matthias; Schmidt, Stefanie (Millennium-Studien / Millennium Studies, 2020)
This volume covers the transition period stretching from the reign of Justinian I to the end of the 8th century, focusing on the experience of individuals who lived through the last decades of Byzantine rule in Egypt before the arrival of the new Arab rulers. The contributions drawing from the wealth of sources we have for Egypt, explore phenomena of stability and disruption during the transition from the classical to the postclassical world.